Media Framing of Political Power in Indonesia: A Study of Tempo Magazine’s “Indonesia 2026” Special Edition - Alif Alqausar (Journal of linguistics, culture and communication, 2026)
This study examines how Tempo Magazine constructs political reality through media framing in its Indonesia 2026 Special Edition. The purpose is to analyze Tempo's interpretation of political power, democratic conditions, and state-society relations during Indonesia's critical phase of political consolidation in early 2026. It positions journalism as an active producer of political meaning rather than a neutral reflection of events. The research employs qualitative framing analysis based on Pan and Kosicki's model, focusing on four textual dimensions: syntactic, script, thematic, and rhetorical structures. Data comprise six purposively selected political articles from the edition's Political Rubric, analyzed through systematic textual reading to identify dominant frames and narrative patterns. Findings reveal Tempo frames early 2026 Indonesia as a landscape of democratic tension, centralized power, and shrinking public criticism space. Evaluative headlines, causal scripting, thematic coherence, and charged rhetoric construct a narrative emphasizing democratic vulnerability and political accountability. This interpretive journalism positions Tempo as a critical watchdog, demonstrating the role of framing in shaping public perceptions of power during political transitions.